HISTORY OF COPYRIGHT RIGHTS IN THE FIELD OF SCIENCE IN UZBEKISTAN - Begaliev Javlonbek Rayimnazarovich (Western European Studies, 2024)
In this article, cases in the history of copyright in our country related to the protection of the works created by representatives of the field of science were analyzed and brought to scientific conclusion through certain sources and archival documents.The authors who conducted such scientific research are given examples of the normative legal framework for the payment of copyright fees for the works they created
Keywords: copyright; Science; Scientific Discovery